2023
DOI: 10.1007/s00439-023-02561-1
|View full text |Cite
|
Sign up to set email alerts
|

Unintended CRISPR-Cas9 editing outcomes: a review of the detection and prevalence of structural variants generated by gene-editing in human cells

Abstract: Genome editing using the clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated protein (Cas) gene-editing system (CRISPR-Cas) is a valuable tool for fundamental and applied research applications. Significant improvements in editing efficacy have advanced genome editing strategies into phase 3 human clinical trials. However, recent studies suggest that our understanding of editing outcomes has lagged behind the developments made in generating the edits themselves. While many r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 73 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…To address this issue, we demonstrated that by delivering a combination of silent and mutant donors (of the same strand to prevent donor annealing) one can re-introduce heterozygosity based on the ratio of donors delivered, allowing editing levels and zygosity to be tuned. Another consideration that would be important for any clinical use of edited cells is off-target editing and genomic rearrangements 29 . We did not observe any off-target edits at predicted sites, regardless of whether edits were done in the presence of AZD7648/p53 siRNA or not, suggesting that the protocol presented here did not substantially increase off-target editing frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, we demonstrated that by delivering a combination of silent and mutant donors (of the same strand to prevent donor annealing) one can re-introduce heterozygosity based on the ratio of donors delivered, allowing editing levels and zygosity to be tuned. Another consideration that would be important for any clinical use of edited cells is off-target editing and genomic rearrangements 29 . We did not observe any off-target edits at predicted sites, regardless of whether edits were done in the presence of AZD7648/p53 siRNA or not, suggesting that the protocol presented here did not substantially increase off-target editing frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations involving the editing of human embryonic stem cells and other cell types have revealed that the Cas9 protein can directly interact with the DNA-PK complex, impeding the DNA repair pathway and potentially heightening the risk of chromosome fragmentation ( 76 ). Moreover, the utilization of the CRISPR-Cas system has the potential to induce unforeseen structural variations (SVs), including deletions, duplications, and insertions ( 77 ). Consequently, CRISPR/Cas9 technology may raise some potential safety issues for CAR-T cell therapy that need to be carefully considered and addressed.…”
Section: Crispr/cas9 Technology and Pcar-t Cellsmentioning
confidence: 99%
“…Fundamental to genome editing systems, such as clustered regularly interspaced short palindromic repeats (CRISPR) and the CRISPR-associated protein (Cas9), is the requisite induction of targeted DNA double-strand breaks (DSBs) to specific base sequences, and subsequent inactivation or replacement of the targeted or closely associated sequences [1][2][3][4]. However, because no genome editing technology or DNA repair pathway is 100% error-free, low-frequency but potentially genotoxic, structural variants are often observed in parallel with the desired edit(s) [5].…”
Section: Introduction Structural Variants Arise From the Mis-repair O...mentioning
confidence: 99%
“…Targeted DSBs induced by guided endonucleases have an increased potential for mis-repair among broken DNA ends since they can be relatively close in time and proximity to other DSBs in the cell. Just as for DSBs induced by other sources, such as ionizing radiations, mis-repair events result in the creation of structural variants, including inversions, deletions, translocations, and even more complex chromosome aberrations [5,[8][9][10]. A simple rearrangement, such as an inversion, requires the mis-repair of two concurrent DSBs, while complex rearrangements involve three or more DSBs, and so the risk of formation of both simple and complex structural variants increases in direct proportion to the number of on-and off-target edits occurring in an individual cell.…”
Section: Introduction Structural Variants Arise From the Mis-repair O...mentioning
confidence: 99%
See 1 more Smart Citation